On the effects of earthquakes in geomagnetic pulsations and their possible nature - Dovbnya, B. V. (Geofizicheskiy Zhurnal, 2011)
As was shown using data from the "Borok" and "College" geophysical observatories, geomagnetic pulsations in the frequency range of millihertz to several hertz demonstrate their response to seismic events. Examples are shown which illustrate the character of seismic activity impact on the regime of various types of pulsations. Different mechanisms of such impact are discussed.